The shaming state: how the US treats its citizens in need - Salman, Sara (New York University Press, 2023)
"The Shaming State is a comparative study of the impact of market fundamentalism on late modern American society. By looking at refugee resettlement and post-disaster relief programs, the book argues that withholding social welfare generates feelings of shame which are transformed into punitive feelings and expressions of hostility against marginalized groups"--